Parâmetros bioquímicos em Eisenia andrei após exposição a pesticidas utilizados no cultivo da soja em solo sob integração lavoura-pecuária - Poerschke, Liliana Beatriz (2023)
Pesticide consumption observed in Brazil in recent years brings a concern about the impact that these molecules may have on the environment. After application, pesticides can have several destinations, including atmosphere, aquatic systems and, mainly, soil. With this contamination, pesticides end up affecting soil fauna, animals and humans, causing an imbalance in the ecosystem. One way to reduce the damage caused by pesticides is by immobilizing the molecules in soil particles and consequently reducing the bioavailability of these chemicals in the soil solution. Increasing the pH and organic matter levels in the soil are ways of controlling the availability of these molecules. The use of sustainable cultivation practices, such as No-Tillage Farming and Crop-Livestock Integration System, provides the increase in these parameters in a sustainable way. The aim of this research was to determine the toxicological potential that an area cultivated with No-Tillage Farming and Crop-Livestock Integration System can have on soil organisms (earthworms Eisenia andrei) through the evaluation of enzymatic biomarkers (catalase, glutathione S-transferase, thiobarbituric acid-reactive substances and acetylcholinesterase). The earthworms were exposed in cylinders containing a sample of soil that was cultivated with soybeans for two crops. Eight treatments were analyzed in triplicate. There was an increase in the enzymatic activity of AChE, CAT and GST, causing stress and oxidative damage, evidenced by the activation of the antioxidant defense system. Treatment 4 (which only contained pesticides) was the one that showed the greatest oxidative damage according to the IBR analysis. The results corroborate the hypothesis that the presence of grazing animals and the practice of liming contribute to a reduction in the adverse effect caused by pesticides. In this way, it was possible to briefly understand the pesticide-soil-organism environmental dynamics and how management practices can reduce the toxicological potential of pesticides. The results found are of great importance for assessing the impact caused by sustainable management practices on the soil and for establishing measures that aim to contribute to the dissemination of these practices, due their potential value for environmental preservation.